2013
DOI: 10.1155/2013/618691
|View full text |Cite
|
Sign up to set email alerts
|

Sex as an Independent Prognostic Factor in a Population-Based, Non-Small Cell Lung Cancer Cohort

Abstract: Females experienced a significantly better survival rate than males independent of treatment, age, year of diagnosis and histology. This was greatest in surgically treated patients and in those with adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
4
15
0
2
Order By: Relevance
“…Studies evaluating the effect of gender on long‐term survival in lung cancer have shown that female patients had longer survival times than male patients . In the present study, male/female ratio was 2.3, and the survival time was longer in female patients than in male patients in line with the literature ( P < 0.0001).…”
Section: Discussionsupporting
confidence: 91%
“…Studies evaluating the effect of gender on long‐term survival in lung cancer have shown that female patients had longer survival times than male patients . In the present study, male/female ratio was 2.3, and the survival time was longer in female patients than in male patients in line with the literature ( P < 0.0001).…”
Section: Discussionsupporting
confidence: 91%
“…The indicators are staging, grading, age, and histopathology. In the study by Pitz et al, [11] the survival rate and prognosis of women with lung adenocarcinoma were significantly better than those of men. In this study, statistical analysis showed that age was not an independent factor affecting prognosis, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The most important unfavorable prognostic factors for lung cancer patients are advanced stage, weight loss, poor performance status non surgical treatment and male gender (Mould and Wiliams, 1982, Ramalingam et al, 1998, Radzikowska et al, 2002, Yang et al, 2001, Pitz et al, 2013. Caldarella et al reported that, among women, survival was significantly better for adenocarcinoma patients than for those with squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%